2005
DOI: 10.1038/sj.leu.2404065
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation in adults with acute lymphoblastic leukemia in first complete remission: analysis of the LALA-85, -87 and -94 trials

Abstract: To evaluate the results of autologous stem cell transplantation (ASCT) in a large population of adults with acute lymphoblastic leukemia (ALL) in first complete remission (CR), we performed an individual data-based overview of the last three trials from the LALA group. Overall, 349 patients with ALL prospectively randomized in the consecutive LALA-85, -87, and -94 trials to receive either ASCT or chemotherapy as post-CR treatment were analyzed. Eligibility criteria were 15-50-year-old patients without sibling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
1
22
0
2
Order By: Relevance
“…However, when the results are examined, focusing on treatment-related mortality and relapse, they are similar to those of recent reports with much shorter follow-up. 8,25,26 The significant advantage of this data set is that it provides long-term follow-up, out to 7 years, for both autologous and URD HSCT, and may aid both physicians and patients in their clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the results are examined, focusing on treatment-related mortality and relapse, they are similar to those of recent reports with much shorter follow-up. 8,25,26 The significant advantage of this data set is that it provides long-term follow-up, out to 7 years, for both autologous and URD HSCT, and may aid both physicians and patients in their clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several phase III studies have failed to demonstrate the superiority of AHCT over conventional chemotherapy. [2][3][4][5] We hypothesized that an intensified approach might improve the outcomes of AHCT for adults with ALL. We used an intensive consolidation treatment with high-dose cytarabine and etoposide that has been used in AHCT for AML and has produced excellent hematopoietic cell mobilization.…”
mentioning
confidence: 99%
“…Even in the International ALL Trial (MRC UKALL XII/ECOG E2993), the administration of a single autoHSCT instead of consolidation treatment resulted in decreased leukemia-free survival (LFS) [10]. On the other hand, the French group revealed that autoHSCT was associated with a lower relapse rate and improved LFS compared to the chemotherapy consolidation [12]. The retrospective analysis of the European Working Group for ALL showed surprisingly good results for autoHSCT among adult ALL patients, if prior to transplantation, the level of minimal residual disease (MRD) is below 0.1% [13].…”
Section: Introductionmentioning
confidence: 99%